Impact of Industrialization on Religious Organizations in Indonesia - Ilyas, Ilyas; Syaifuddin, Muh; Siswanto, Yudi (Universitas Negeri Semarang, 2022)
The era of globalization has impacted religious organizations whose members are village youths working in the industry in the Jepara region. This study aims to determine the impact of industrialization and the factors that influence the interest of Geneng village in joining religious organizations. This study uses a descriptive approach. The research subjects were the chairperson, treasurer, secretary, members, trainers, and youth as informants. Data collection techniques using observation, interviews, documentation. The data validity technique uses source triangulation. Data analysis techniques collect, reduce, present, and draw conclusions. The results showed that Geneng village youth's interest in religious organizations was still low due to a lack of publications, employment, youth environment, and education. Meanwhile, regarding social impacts, the intensity of activity and members' interest decreased. At the same time, the economic aspect of members who are already working in the industry provides material assistance during the activity. This study concludes that the interest of Geneng village youth is still low due to a lack of publications, employment, environmental, youth associations, and educational factors. Meanwhile, industrialization impacts religious organizations in social and economic aspects. The researchers suggest that publications are maximized again, and members can manage their time well.